Luz, câmera, emoção: um encontro com “Tito e os pássaros” - Silva, João Victor Torres da (2023)
Through angles, sequences and scenes, this research accompanies the story of the boy Tito, protagonist of the Brazilian animation “Tito and the birds” (2019), who, together with his two best friends, Sara and Buiu, live an adventure journey to discover the cure for a strange epidemic that turns everyone who feels fear to stone. The characters live in a society that, like ours, lives in a chaotic atmosphere, of instabilities and illness. In this sense, the study is based on how the filmic narrative, under the eyes of the boy Tito, helps us to think about the use of images and emotions as a form of social control? For the production of data, the study was inspired by screen ethnography, a methodological posture that unsettles our tamed eyes, building unlearning about what we take as “natural”, locating other possibilities of positioning, entering other spaces, other reflections, forging other forms to look around us; running away from cliché-images, watchwords and super-obedience.